Pengaruh Pemberian Aromateraphy Pappermint terhadap Kecemasan Ibu Hamil Trimester III Menghadapi Persalinan - Wirani Wirani; Mudy Oktiningrum; Nella Vallen Ika Puspita (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
Pregnancy lasts from ovulation to parturition for approximately 280 days (40 weeks) and no more than 300 days (approximately 43 weeks). In the first trimester of pregnancy, most women experience discomfort due to anatomical and physiological changes, such as nausea, vomiting, cravings, fainting, changes in the skin and breasts, anorexia, and increased frequency of urination. When entering the third trimester, many pregnant women begin to experience anxiety before giving birth. This study aims to determine the effect of peppermint aromatherapy on the level of anxiety of pregnant women in the third trimester in facing childbirth. The research method used is a quantitative method with a descriptive approach. The sampling technique used is total sampling, and data analysis is carried out using the Wilcoxon test, a non-parametric test. The results of the study showed that there was a significant effect of peppermint aromatherapy in reducing the level of anxiety of pregnant women in the third trimester before giving birth, as evidenced by a p-value of 0.000 (<0.05). Peppermint aromatherapy has been shown to be effective as a non-pharmacological intervention.